UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS SATU PADA MATA PELAJARAN BAHASA INDONESIA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN KARTU KATA BERGAMBAR UPT SDN BATURETNO 1 - Matina, Maila Shofiyatunnajja (Jurnal Tunas Pendidikan, 2025)
This research focuses on boosting the learning abilities of first-grade students in Indonesian language classes by incorporating visual aids in the form of illustrated word cards as a supportive learning tool. The reason for conducting this research is due to the low interest and ability of students to read, which is caused by teaching methods that are still conventional and do not encourage active participation of students. The research was carried out through a Classroom Action Research (CAR) approach, involving two cycles. Each cycle comprised four steps: planning, execution, monitoring, and assessment. The subject of this research consisted of thirteen students from the first grade of UPT SD Negeri Baturetno 1, Tuban District, Tuban Regency. Data was obtained using a test sheet. The results of this study showed that the average score increased from 59.23 in the pre-cycle to 70.31 in cycle I then to 81.15 in cycle II. In addition, the percentage of successful student learning outcomes increased from 23% in pre-cycle to 84.6% in cycle II. This study proves that picture word card media can effectively improve the learning outcomes of first grade students.